PENERAPAN E-COMMERCE UNTUK MENINGKATKAN DAYA SAING UMKM JENANG KUDUS - Daniel Alfa Puryono; Sekar Ayu Merisda; Ninik Haryani (Electro Luceat, 2022)
This study discusses the important role of implementing E-commerce. As well as its benefits in increasing competitiveness for MSMEs Jenang Kudus. Because MSMEs have enormous potential to encourage economic growth and development in our country. On the other hand, there are still many small business actors who have not been able to take advantage of the ease of promotion through various online-based media. Therefore, to make it easier for the business actors, an E-commerce application was created and managed by a separate business entity in the future. So that business actors are no longer confused because they don't understand making an attractive website, confused because they don't have the capital to create and manage a website or customer database. So they can stay focused on their business. The results of application trials with the existence of E-commerce, can encourage consumer interest to transact with Jenang Kudus business actors wherever and whenever. In addition, the results of the study also show that economic, social and environmental impacts can also be correlated with competitiveness. So that in the future it is recommended to use various methods for data analysis, for example a combination of quantitative and qualitative so as to increase the potential for findings.